111 Adipose Tissue-Derived Mesenchymal Stem Cells as a Potential Restorative Treatment for Cartilage Defects: A PRISMA Review and Meta-Analysis. (19th August 2022) - Meng, H; Lu, V; Khan, W
Abstract: Aim: Joint damage through trauma or degeneration causes cartilage defects, leading to osteoarthritis (OA). Current therapies relieve symptoms or replaces damaged joint, which is costly and fraught with complications. Mesenchymal stem cells (MSCs) have immunomodulatory properties and low immunogenicity, making them a novel avenue for research for OA treatment. This systematic review investigates whether adipose derived MSC (AMSCs) can treat cartilage defects. Method: A systematic search was performed on MEDLINE, EMBASE, Cochrane Library, Scopus, Web of Science. Clinical, imaging, functional outcomes were extracted from nineteen included studies. Inclusion criteria was studies conducted on human populations that compared effects of AMSCs on cartilage regeneration to non-exposed controls. Studies conducted on animals, ex vivo studies, in vitro studies were excluded. Results: Nine studies reported improved Visual Analogue Scale (VAS) scores (mean difference -3.30; 95% CI:-3.72, -2.89; p<0.001). Eight studies reported improved Knee injury and Osteoarthritis Outcome Score (KOOS) in five subscales. Pooled analysis of Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores in seven studies revealed an improvement (mean difference -25.52; 95% CI:-30.93, -20.10; p<0.001). Cartilage regeneration was assessed using Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score. All studies reported improved regeneration, with a pooled end-point score of 68.12 (95% CI:62.18–74.05; p<0.001). Conclusions: AMSCs are effective therapeutic agents for cartilage defects. We recommend researchers to determine roles of biochemical components that facilitate AMSC-mediated cartilage repair. Establishing the most efficient methods for MSC extraction, culture, delivery, and performing studies with long follow-up times enable future research to provide evidence needed to bring AMSC-based therapies into the market.